A case of isolated axillary tuberculous lymphadenitis - Pandiaraja Jayabal (Nigerian Journal of Medicine, 2020)
Tuberculosis (TB) is one of the communicable diseases with high morbidity to the patient. TB is divided into pulmonary and extrapulmonary TB. In extrapulmonary TB, isolated axillary TB is rare and sometimes creates diagnostic difficulty, particularly in female patients. The axillary lymph nodes are affected in around 3% of tuberculous lymphadenitis. Our case presented with isolated axillary tuberculous lymphadenitis which is rare without evidence of TB elsewhere in the body. It is more common in females compared to males, and it commonly involves the left side. Most of the cases do not show systemic manifestations. Chest X-ray and ultrasound are useful primary investigations for the diagnosis. Histopathological examination of the lymph node is the confirmatory test for axillary tuberculous adenitis. Hence, tuberculous lymphadenopathy should be considered one of the differential diagnoses in a female patient with isolated axillary lymphadenopathy even without clinical manifestations of TB.